2020
DOI: 10.3889/oamjms.2020.4569
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Imbalance in Women with Infertility Caused by Polycystic Ovary Syndrome: Is There a Connection with Body Mass Index?

Abstract: BACKGROUND: The most common cause of female infertility is ovulation disorders, and the most common non-ovulatory cause is polycystic ovary syndrome (PCOS). AIM: The aim of the study was to define the reproductive hormone levels in women with infertility due to PCOS, depending on the body mass index (BMI). PATIENTS AND METHODS: The present study involved 100 women aged 25–39 years with infertility due to PCOS (PCOS group) and 30 women of the same age with infertility due to tubal-peritoneal causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 42 publications
3
8
1
Order By: Relevance
“…This may be explained by the theioryical that some PCOS pathogenesis connected to deficient hypothalamic dopaminergic activity, also responsible for raises LH/FSH ratio and thyroid stimulating hormone (Anthony et al, 1984). Furthermore, testosterone with high level in women infected with PCOS proposed that induced or genetic excess of testosterone may be the main cause of obesity relationship with PCOS (Khmil & Marushchak, 2020). Thus, our results are agreement with the recent studies and confirm the importance of hormonal evaluation for PCOS for evolution early to prevent long-term reproductive problems and infertility.…”
Section: Discussionsupporting
confidence: 92%
“…This may be explained by the theioryical that some PCOS pathogenesis connected to deficient hypothalamic dopaminergic activity, also responsible for raises LH/FSH ratio and thyroid stimulating hormone (Anthony et al, 1984). Furthermore, testosterone with high level in women infected with PCOS proposed that induced or genetic excess of testosterone may be the main cause of obesity relationship with PCOS (Khmil & Marushchak, 2020). Thus, our results are agreement with the recent studies and confirm the importance of hormonal evaluation for PCOS for evolution early to prevent long-term reproductive problems and infertility.…”
Section: Discussionsupporting
confidence: 92%
“…It is well known that obesity and visceral adiposity worsen the clinical features of menstrual irregularity and infertility 35 and they are correlated with increased serum androgens and LH in female with PCOS. 36 In this study treatment of the PCOS with flavonolignan silibinin displayed the potential alleviation of the hormonal abnormalities and restored the normal estrous cyclicity in the rats. Silibinin treated groups alone and in combination with metformin, did not display any significant increase in body weight compared with the animals in the different groups, which suggested that silibinin might have the suppressive effect on lipid accumulation in adipocytes.…”
Section: Discussionmentioning
confidence: 73%
“…It is well known that obesity and visceral adiposity worsen the clinical features of menstrual irregularity and infertility 35 and they are correlated with increased serum androgens and LH in female with PCOS. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Gonadotropic dysfunction and insulin resistance are the primary pathophysiological elements of polycystic ovarian syndrome (PCOS), and both are frequently linked to high body mass index. Menstrual, ovulation, and infertility issues have been linked to obesity (Khmil et al, 2020).…”
Section: Informant Consensus Factormentioning
confidence: 99%